The Analysis Of Directive Speech Acts Used In The English Textbook “Pathway To English” For Senior High School Grade X - Aulia Putri Rahmawati; Eka Fanti Sulistiyaningsih (Journalistics: Journal of English Teaching and Applied Linguistics, 2021)
Communication is one way to express our minds, feelings, ideas, and emotions. There are speakers, messages or information, and listeners in communication. In giving information, we use language to make the listeners or the reader understand our information. The way someone convinces the listeners can be studied in speech act theory. So, the speech act is how to do something through word or utterance. This research aims to find out the types of directive speech acts and to find out the most frequent directive speech act used in the English textbook “Pathway to English” for senior high school grade X. The data was collected from the English textbook “Pathway to English” for senior high school grade X. This research is included in qualitative research. The result of this research showed that there are three types of directive speech act, they are command, request, and suggestion. The percentage was found highest in suggestion 82% or equals 29 suggestion.